2014
DOI: 10.1212/wnl.0000000000000707
|View full text |Cite
|
Sign up to set email alerts
|

Meta-analysis in more than 17,900 cases of ischemic stroke reveals a novel association at 12q24.12

Abstract: Objectives:To perform a genome-wide association study (GWAS) using the Immunochip array in 3,420 cases of ischemic stroke and 6,821 controls, followed by a meta-analysis with data from more than 14,000 additional ischemic stroke cases.Methods:Using the Immunochip, we genotyped 3,420 ischemic stroke cases and 6,821 controls. After imputation we meta-analyzed the results with imputed GWAS data from 3,548 cases and 5,972 controls recruited from the ischemic stroke WTCCC2 study, and with summary statistics from a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
64
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(67 citation statements)
references
References 23 publications
(33 reference statements)
1
64
1
Order By: Relevance
“…10 Another, the 12q24.12 locus, was first identified as a novel association with all ischemic stroke subtypes and was not mediated by conventional cardiovascular risk factors. 9 However, a recent study demonstrated that the 12q24 locus was specifically associated with the small artery occlusion stroke subtype, rather than for all stroke subtypes. 11 These data highlight the potential involvement of the ALDH2 gene in the risk of ischemic stroke.…”
Section: Discussionmentioning
confidence: 97%
“…10 Another, the 12q24.12 locus, was first identified as a novel association with all ischemic stroke subtypes and was not mediated by conventional cardiovascular risk factors. 9 However, a recent study demonstrated that the 12q24 locus was specifically associated with the small artery occlusion stroke subtype, rather than for all stroke subtypes. 11 These data highlight the potential involvement of the ALDH2 gene in the risk of ischemic stroke.…”
Section: Discussionmentioning
confidence: 97%
“…In selecting IS associated SNPs, we considered the five loci (9p21, HDAC9, PITX2, ZFHX3 , and 12q24.12 ) associated with stroke in METASTROKE and in a recent publication 38, 39. We set a p ‐value threshold of p  = 0.01 to determine significance, using the Bonferroni method to correct for five independent tests.…”
Section: Participants and Methodsmentioning
confidence: 99%
“…Detection of a significant association does not mean that the identified SNP is causal; it is usually merely a marker for a causal functional SNP that is located on a nearby region of the genome. ); monomorphic in white populations, and no association between this gene region and stroke was found in the METASTROKE study 20 All ischaemic stroke 27,29 12p13 12q24…”
Section: Implications For the Clinicianmentioning
confidence: 97%
“…20,28 The first association of a genetic variant with all types of ischaemic stroke to be replicated convincingly was reported with a locus at 12q24 (OR 1.1). 29 The same gene region has been associated with cardiovascular risk factors, including hypertension and type 1 diabetes mellitus, 29 although the SNP associated with these diseases was not the same as that found to be associated with stroke. The mechanism of action, and whether or not the association occurs independently of or via conventional risk factors, is not clear.…”
Section: Small-vessel Disease (Lacunar Stroke)mentioning
confidence: 99%